The Clinical Features of Patients with Chronic Hepatitis C Virus Infections Are Associated with Killer Cell Immunoglobulin-Like Receptor Genes and Their Expression on the Surface of Natural Killer Cells - Podhorzer, Ariel; Dirchwolf, Melisa; Machicote, Andrés; Belen, Santiago; Montal, Silvina; Paz, Silvia; Fainboim, Hugo; Podestá, Luis G.; Fainboim, Leonardo (Frontiers in Immunology, 2018)
KIR genes are known to play a role in the acute phase of hepatitis C virus infection. The present study investigated their roles in chronic HCV (CHCV) infection by analysing the phenotypes and function of NK and T cells that express KIRs. T cells from CHCV patients showed a more differentiated phenotype, and NK cells exhibited an activated profile. These observations are consistent with the increased expression of the degranulation marker CD107a observed after PMA stimulation. We explored the correlations between the expression of KIR genes and lectin type-C receptors with clinical factors that predict progression to fibrosis and cirrhosis. The expression levels of KIR2DS3 and the functional alleles of KIR2DS4-FL were increased in patients with intermediate and high viral loads. Homozygous KIR2DS4 was also associated with the presence of cirrhosis. In the group of individuals with a shorter infection time who developed cirrhosis, we detected decreased expression of KIR3DL1 in CD56dim NK cells in the presence of its ligand. Similarly, in the group of patients with late CHCV infections complicated with cirrhosis, we detected lower expression of the strong inhibitory receptor NKG2A in CD56bright NK cells. We also detected an increase in NKG2C expression in CD56dim NK cells in CHCV patients who displayed high necroinflammatory activity. Decreased KIR3DL2 expression in CD56dim and CD56 bright NK cells was associated with a high BMI, and KIR3DL2 expression may be one factor associated with the more rapid progression of CHCV to fibrosis in patients. Importance Our results indicate that increased expression of an activated receptor or decreased expression of the inhibitory counterpart may be associated with a worse clinical evolution during the chronic phase of the HCV infection, in contrast to the acute phase of HCV infection. These changes should be evaluated in the context of a more differentiated/activated state of peripheral blood and liver T cells and NK cells and their increased capacity to degranulate, which may reflect a potential increase in cytotoxic activity.